Adequate nutrition in the light of international law (2022)
This research seeks to analyze the concepts and elements that structure the right to food, as well as the sources that serve as parameters by which States must be guided when developing their internal regulations. It was a dogmatic investigation of general scope. For this, the methodology of legal sciences was used with support in the documentary technique. The research showed that the very concept of the human right to adequate food has been evolving and has expanded to other situations that go beyond the traditional view of living free from hunger. Likewise, the right to adequate food has a collective and transversal dimension from the moment it is incorporated into concepts such as food sovereignty and security, and food systems.